Оптимізація використання матеріальних ресурсів галузі рослинництва - Масляєва, Ольга Олександрівна; Masliaieva, Olga; Гурін, Тетяна Юріївна; Hurin, Tat`yana; Закревська, Діана Олександрівна; Zakrevskaya, Diana (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2025)
У статті досліджено питання оптимізації використання матеріальних ресурсів у сільськогосподарському підприємстві ТОВ "КСГ Дніпро". Проаналізовано динаміку посівних площ у 2022-2024 роках, виявлено тенденції змін у сівозміні та вплив цих змін на ефективність виробництва. Визначено основні чинники, що впливають на рівень використання матеріальних ресурсів, зокрема технологічні процеси, управлінські рішення та інноваційні підходи до господарської діяльності. Детально розглянуто структуру витрат підприємства та їхню динаміку, що дозволило виявити ключові напрямки оптимізації. Встановлено, що впровадження точного земле-робства, автоматизації процесів та економіко-математичного моделювання сприяє зниженню витрат і підвищенню ефективності використання ресурсів. Обгрунтовано доцільність застосу-вання математичних моделей для прийняття ефективних управлінських рішень. Дослідження підтвердило, що оптимізація матеріальних ресурсів є ключовим фактором підвищення конку-рентоспроможності та фінансової стабільності підприємства. The article examines the optimization of material resource utilization as a crucial factor in enhancing the efficiency of crop production. Based on the case study of LLC "KSG Dnipro," the research provides a comprehensive analysis of changes in sown areas from 2022 to 2024, identifying key trends in crop structure transformation and their impact on economic performance. The study highlights the significance of technological processes, managerial decisions, and innovative approaches in improving resource efficiency and reducing production costs. A detailed financial analysis of LLC "KSG Dnipro" is conducted, showing fluctuations in key economic indicators, including revenue, production costs, and profitability. The study reveals that despite an increase in total expenditures, effective cost management and optimized resource allocation can mitigate financial risks and improve the company's economic resilience. Special attention is given to the impact of rising administrative and marketing expenses, which necessitate strategic cost control and investment planning. The research also explores the application of economic-mathematical modeling as a valuable tool for optimizing resource allocation. By implementing linear programming and other quantitative methods, agricultural enterprises can maximize their revenue while maintaining a balanced cost structure. The study proposes a framework for developing an optimization model that considers various constraints, including available land resources, input costs, and expected market conditions. The findings confirm that rational material resource management is essential for ensuring financial sustainability and competitiveness in the agricultural sector. Effective optimization strategies enable enterprises to achieve higher productivity, reduce unnecessary expenditures, and enhance overall economic efficiency. The study emphasizes the importance of adopting innovative agricultural technologies, improving management practices, and continuously analyzing cost structures to maintain long-term profitability. In conclusion, the research underscores that optimizing material resource use is a fundamental driver of economic growth in crop production. The integration of advanced technologies, data-driven decision-making, and precise resource management fosters greater resilience in agricultural enterprises. Future research should focus on refining economic models and exploring additional strategies for enhancing production efficiency in the face of evolving market challenges.
Optimization of material resources use plant growing industry
Keywords: матеріальні ресурси; material resources; економічна ефективність; economic efficiency; витрати на виробництво; production costs; рентабельність; profitability; оптимізація розподілу ресурсів; resource allocation optimization; агробізнес; agribusiness